Frequency of Anaemia in Patients with Musculoskeletal Pain - Fatih Baygutalp; Ayhan Kul (Galenos Yayinevi, 2020)
Objective:This study aimed to determine the frequency of anaemia in patients with musculoskeletal pain who were admitted to our clinic.Materials and Methods:Three hundred and thirty-eight patients with musclosketal pain were divided into 2 groups as follows: Group 1, with diffuse pain, and group 2, with local pain. Serum iron, ferritin, total iron-binding capacity, vitamin B12 and plasma haemoglobin levels were analysed retrospectively.Results:Patients with iron deficiency and iron-deficiency anaemia were evaluated retrospectively. There was iron deficiency in 35.7% of all patients with musculoskeletal pain and iron-deficiency anaemia in 11.2% of all patients. Iron deficiency was identified in both groups when the patients were evaluated separately according to the painful area. The rates of iron deficiency in the groups were 28.3% in the diffuse pain group and 37.1% in the local pain group.Conclusion:We suggest that serum iron and ferritin levels should be measured, and if necessary, supplemented for better treatment success in patients with musculoskeletal pain.